229k views
4 votes
3) y = (x - 2)² + 1​

User Hoang Pham
by
5.0k points

2 Answers

3 votes

Answer:

x = square root y - 1 + 2

x = square root -y - 1 + 2

Explanation:

*Hint ^ means squared

Subtract 1 from both sides.

y - 1 = (x-2) ^2

Take the square root of both sides.

+- square root of y - 1 = x - 2

Switch sides.

x-2= +- +- square root of y - 1

​​

Break down the problem into these 2 equations.

x-2= square root y - 1

x-2= square root -y - 1

Get the "x" by itself

x = square root y - 1 + 2

x = square root -y - 1 + 2

Hope this helps!!! Good luck!!! ;)

User Reza Ebrahimi
by
5.1k points
7 votes

Answer:

Step 1: Divide both sides by 3.

3y

3

=

x2−4x+5

3

y=

1

3

x2+

−4

3

x+

5

3

Answer:

y=

1

3

x2+

−4

3

x+

5

3

Explanation:

User LeRoy
by
5.4k points